Experimental study of the effect of load and vehicle speed on energy consumption of electric vehicles, Faculty of Engineering, University of Mataram - I.M. Mara; H.S. Tira; T. Rachmanto; I.M. Nuarsa (Universitas Mataram, 2025)
The use of electrical energy for vehicles is currently very relevant because its efficiency is relatively high and is environmentally friendly, due to, it does not emit exhaust gases emission. Indonesia has a huge potential to develop electric vehicles because there is a lot of nickel available to be processed into batteries. However, it is necessary to consider the level of energy use of the electric vehicle that will be made. How much does speed influence the use of electrical energy, or at what speed does an electric vehicle provide the greatest efficiency in energy use. This research is intended to study how much vehicle speed influences energy consumption and also to obtain the vehicle speed range with the lowest energy use efficiency in autonomous electric vehicles, Faculty of Engineering, University of Mataram. The lowest energy consumption occurs at a speed of 20 km/h with a load of 960 kg, which is 0.173 kWh/km. The most efficient speed for distance traveled per kWh is 30 km/h, regardless of vehicle weight. A speed of 40 km/h decreases efficiency, especially with a heavier load, while increasing the load at lower speeds (20 km/h and 30 km/h) does not significantly reduce efficiency, and even slightly increases the distance traveled.